The Relevance of Ibn Khaldun's Islamic Education Concept to Modern Education on the book of Muqaddimah - Fariha; Hafidz; Yuka Afilsa; Nadhine; Jennygiyanadivaa; Mugsith Ariyanto; Muhammad Hanan Imaduddin; Zaky Hafidz Abdillah (Bulletin of Islamic Research, 2025)
Ibn Khaldun is a Muslim intellectual who has multiscience and expertise. He is known as a historian, sociologist, politician, and even a philosopher. However, in his monumental work, Muqaddimah, Ibn Khaldun also had insightful thoughts about education that he wrote almost one-third of the content of the Muqaddimah. Therefore, he deserves to be called an Islamic educational figure. Since Ibn Khaldun was a Muslim intellectual who had no doubt about his knowledge of Islamic studies, it was interesting to examine his views on Education which in many ways were certainly influenced by his understanding of Islamic teachings in addition to the problems and realities of the ummah in his time. His religious, critical and humanist educational thinking can be a reference for the development of Islamic education, especially in the National Education System in Indonesia, especially in the current era where the development of science tends to be oriented towards the Western concept (west-centric), including the field of education.